Anti-Crisis Fiscal Adjustment under the Conditions of Martial Law and Post-War Recovery in Ukraine - Iefymenko, Tetiana (Public Governance, Administration and Finances Law Review, 2022)
In global practice, uncontrolled imbalances in the fiscal space are a real threat to a country’s financial security in the context of the new economic reality; destabilisation challenges as well as the risks of the spread of crisis phenomena under the conditions of uncertainty and geopolitical conflictogenity. Applying the results of theoretical and practical research based on the methods of factual and statistical analysis, it was determined that under conditions of modern full-scale turmoil, all components of fiscal regulation should be focused on the priorities of resilience in the period of martial law and sustainable development in post-war recovery. As a candidate for acceding the European Union, Ukraine will carry out reforms that will bring the country closer to world standards in all areas of financial relations. Therefore, the processes of reforming tax systems, including administrative regulations, should be focused on solving systemic institutional problems of change management.